(untitled) (AYUSHDHARA, 2019)
Arshas is one of the most common Ano-rectal disorders. Yet a perfect treatment modality without side effects and with long term relief has been a challenge. Acharya Sushruta has mentioned four treatment methods for Arshas such as Aushadha, Kshara, Agni and Shastra karma. Among the four modes of treatments mentioned, Aushadha causes the least discomfort to the patient psychologically, physically and economically. Hence effective management of Arshas using an Aushadha is needed. Objectives: The study is aimed to evaluate the effect of Chiravilwadi kashayam in the management of Arshas w.s.r. to Interno-external Haemorrhoids. Method: It is a single blind, pre test & post test design where 30 cases diagnosed as Arshas w.s.r. Interno-external Haemorrhoids were selected and recorded. Result: Internal administration of Chiravilwadi Kashayam for a month with a pinch of Saindhava and Luke warm water as Anupana showed highly significant result in reduction of the signs and symptoms of Arshas. Interpretation: The clinical symptoms of Arshas is Bleeding per rectum, Mass per rectum, Constipation, Pain, Pruritus and Aruchi. Arshas is a Tridoshaja Vyadhi which is seen mainly in people with irregular food habits and sedentary lifestyle. Hence Arshogna Drug along with proper intake of leafy green fibrous food is ideal. Conclusion: Chiravilwadi Kashayam is an excellent remedy for Arshoroga. The combination of Chiravilwadi Kashayam has all the qualities required for Arshogna dravya which are Anulomana, Ama pachana, Agni Deepana property and importantly Arshogna property.